Pelatihan Islamic Goal Setting untuk Meningkatkan Efikasi Diri Siswa dalam Pengambilan Keputusan Karier - Hedy Liana; Yulia Hairina; Shanty Komalasari (Faculty of Psychology, Sunan Gunung Djati Islamic State University of Bandung, 2022)
This study aims to examine the effect of Islamic Goal Setting Training to increase self-efficacy in career decision making for students in MAN 1 Model Banjarmasin. This study used a quasi-experimental study, with a non-randomized pretest-posttest control group design. The sample was recruited using purposive sampling which was divided into experimental and control groups each consisting of 10 people. Analysis of the results using the Mann-Whitney non-parametric test shows that there is a difference in the score of the level of self-efficacy in career decision making between the experimental group and the control group. The experimental group experienced an increase and the control group experienced a decrease. Thus, Islamic Goal setting training may affect the increase of self-efficacy in students' career decision making.